Pengembangan Biosensor Berbasis Kertas untuk Penentuan Aktivitas Antihiperlipidemia Pada Sampel Ekstrak Tanaman - Vinda Aisya Vira; Bambang Kuswandi; Indah Purnama Sary (Pustaka Kesehatan, 2021)
A biosensor is an alternative method to determine the antihyperlipidemic activity to be more simple, effective, and efficient in various herbal extracts. This study aimed to develop a biosensor with the principle of pancreatic lipase enzyme inhibition in paper microzone plates using Whatman filter paper for the matrix, 200 unit/mL of lipase enzyme solution, 1% extract, and 80 mM p-NPB substrate. This paper-based biosensor method shows results that fulfilled the several characterizations, that are the 30 min of the incubation time; linearity using 7 standards orlistat concentrations of 5-35 mg/mL with the regression equation of Y= 22.09585 + 2.170514X, correlation coefficient value (r)= 0.9996745, Vx0= 1.509906%, Xp= 1.572533 mg/mL; LOD and LOQ are 1,573 mg/mL and 4,718 mg/mL; precision with RSD value of 2.545%; accuracy with % recovery value of 99.222%; biosensor usage time after storage remained stable for 3 days at chiller temperatures and for 45 minutes at room temperature. The paper-based biosensor can be an alternative method for detecting antihyperlipidemic activity in plant extracts as same as UV-Vis spectrophotometry method.